Secret Agent Jack Stalwart. [book 2], The Search for the Sunken Treasure : Australia - Singer Hunt, Elizabeth (Red Fox, 2006)
Off the coast of Australia, a diver has vanished and along with him an unknown treasure from the wreck of the HMS Pandora. Can Secret Agent Jack Stalwart find the diver and defeat a deadly band of pirates before they sail away with the treasure for ever?